2014
DOI: 10.1177/0022034514528211
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cilia Integrate Hedgehog and Wnt Signaling during Tooth Development

Abstract: Many ciliopathies have clinical features that include tooth malformations but how these defects come about is not clear. Here we show that genetic deletion of the motor protein Kif3a in dental mesenchyme results in an arrest in odontogenesis. Incisors are completely missing, and molars are enlarged in Wnt1 Cre+ Kif3a fl/fl embryos. Although amelogenesis and dentinogenesis initiate in the molar tooth bud, both processes terminate prematurely. We demonstrate that loss of Kif3a in dental mesenchyme results in los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 29 publications
(32 reference statements)
1
59
0
Order By: Relevance
“…Bar: 1 μm and Wnt families (20). In particular, it is known that the primary cilia are associated with Shh and Wnt signaling during tooth development (7). Therefore, our data further support the possibility that the primary cilia are involved in the epithelium-mesenchymal interaction in the enamel knot.…”
Section: Primary Cilia In Tooth Germsupporting
confidence: 80%
See 2 more Smart Citations
“…Bar: 1 μm and Wnt families (20). In particular, it is known that the primary cilia are associated with Shh and Wnt signaling during tooth development (7). Therefore, our data further support the possibility that the primary cilia are involved in the epithelium-mesenchymal interaction in the enamel knot.…”
Section: Primary Cilia In Tooth Germsupporting
confidence: 80%
“…The primary cilia play critical roles associated with the epithelium-mesenchyme interaction in various tissues, including the tooth germ (2,7,17). Accumulating evidence shows that many growth factors/ receptors and cross-talk via these factors between adjacent tissues precisely regulate tooth development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synergetic interaction was postulated by Day et al (76), who reported that Ihh signaling is activated at an early stage of osteoblast maturation during fracture repair, and that Wnt signaling is subsequently upregulated in differentiated osteoblasts. Further research has indicated that the deletion of the motor protein kinesin family member 3A in dental mesenchyme results in the suppression of Hh and activation of Wnt, affecting incisor and molar development (77). These findings may reveal as association between the two signaling pathways at the gene level.…”
Section: Interaction Between Hh and Wnt Signaling Promotes Embryogenementioning
confidence: 95%
“…Similarly, tooth buds from Wnt1-cre Kif3a f/f mice exhibit a loss of HH signaling and a concomitant gain of WNT/β-catenin signaling in the dental mesenchyme. The gain of Wnt signaling in the mesenchyme has a secondary effect on the dental epithelium, where it increases proliferation and results in multiple invaginations instead of single secondary enamel knot (Liu et al 2014). These data suggest that the primary cilium integrates WNT and SHH signaling between epithelium and mesenchyme during odontogenesis (Liu et al 2014).…”
Section: Deficiencies In Odontogenesis Caused By Defective Primary CImentioning
confidence: 97%